Efektivitas dana desa untuk pengembangan potensi ekonomi berbasis partisipasi masyarakat di Desa Bangunjiwo - Atmojo, Muhammad Eko; Fridayani, Helen Dian; Kasiwi, Aulia Nur; Pratama, Mardha Adhi (Universitas Muhammadiyah Ponorogo, 2017)
Community empowerment is part of economic development in Indonesia. As one of strategy to empower the community is by establishing the rulal allocation fund by government as mentioned on â€œUndang-Undang Nomor 6 Tahun 2014â€ about rural. Therefore, the â€œUndang-Undang Nomor 6 Tahun 2014â€ came along with rural allocation fund hopefully might be able to increase the participation of rural community to developing economic condition in order to establish community prosperity. This research used the qualitative method, obesrvation, interview, also documentation. This research aim to analyze the effectiveness of rural fund allocation toward society empowerment, particularly in economic aspect based on community participation in Bangunjiwo Village. Therefore, this research shows that first, the utilization rural fund allocation is most effective for development of economic potential. Second, Bangujiwo Village provider the training for communityâ€™s activity ini order to increasing the economic potential. The last, the mainly economic potential in Bangujiwo Village is called â€œKajigelemâ€.